The relationship between educational attainment, lifestyle, self-rated health, and depressive symptoms among Chinese adults: a longitudinal survey from 2012 to 2020 - Xiong, Xinyan; Hu, Rita Xiaochen; Ning, Wenyuan (Frontiers in Public Health, 2024)
Education holds significant implications for individual health. This work aims to examine the relationship between educational attainment, lifestyle, self-rated health, and depressive symptoms among Chinese adults. We used China Family Panel Studies data from 2012 to 2020. Multiple linear regression models were used to explore the relationship between educational attainment and self-rated health and depressive symptoms, where multidimensional lifestyle (sleep time, exercise time, overtime time, leisure time, housework time, and protein intake) was the mediator variable of the above relationship, and the causal step method was used to test the mediating effect. Our findings show that educational attainment is associated with higher levels of self-rated health and lower levels of depressive symptoms. More importantly, educational attainment also indirectly affects individuals’ self-rated health and depressive symptoms through lifestyle. These findings reveal health interventions to develop education further and improve its quality.